The Free Amino Acid Composition of The Sudanese Fermented Camel's Milk (Garris) - A. Alyan, Abdallah; E. Sulieman, Abdel Moneim; A. Elkhalifa, Elamin (Gezira Journal of Engineering and Applied Sciences, 2009)
Many  workers   have   investigated  the  composition  of  milk and milk   proteins   of   various   species  of   domestic   animals   but   the information regarding  the composition of  fermented  camel 's   milk is  still  limited. The  fresh  camel  milk  contains 3.3-4.7% protein, 2.8 - 3.6%  fat, 4.0 - 5.2%  lactose,  0.7%  ash, 9.2 - 15.4% total solids,  and  to has  a  pH of  6.0-6.5  (Abdel  Rahim, 1987). The casein of camel  milk  is  richer  in  proline  and   threonine than cow's  milk, but poorer in alanine, arginine, glycine and serine (Hoeller and Hassan, 1965).